How I treat relapsed acute lymphoblastic leukemia in the pediatric population - Hunger, Stephen P; Raetz, Elizabeth A (Blood, 2020)
Relapsed acute lymphoblastic leukemia (ALL) has remained challenging to treat in children, with survival rates lagging well behind those observed at initial diagnosis. Although there have been some improvements in outcomes over the past few decades, only ∼50% of children with first relapse of ALL survive long term, and outcomes are much worse with second or later relapses. Recurrences that occur within 3 years of diagnosis and any T-ALL relapses are particularly difficult to salvage. Until recently, treatment options were limited to intensive cytotoxic chemotherapy with or without site-directed radiotherapy and allogeneic hematopoietic stem cell transplantation (HSCT). In the past decade, several promising immunotherapeutics have been developed, changing the treatment landscape for children with relapsed ALL. Current research in this field is focusing on how to best incorporate immunotherapeutics into salvage regimens and investigate long-term survival and side effects, and when these might replace HSCT. As more knowledge is gained about the biology of relapse through comprehensive genomic profiling, incorporation of molecularly targeted therapies is another area of active investigation. These advances in treatment offer real promise for less toxic and more effective therapy for children with relapsed ALL, and we present several cases highlighting contemporary treatment decision-making.